INTELLIGENT PASSWORD AUTHENTICATION FOR AVOIDING SHOULDER SURFING AND BRUTE FORCE ATTACKS - Mrs. Arti Suryavanshi; Prof. Prashant Suryavanshi; Prof. Mrs. Vidya Jagtap (International Journal of Innovations in Engineering Research and Technology, 2021)
Tremendous security measures are based on difficult challenges that can be solved only by mathematicalcomputations and analysis. Latest paradigm for higher security is based on hard artificial Intelligence problems, yet unexplored. In this paper, A novel technique of authenticating users through virtual random keyboards and two level intelligent authentication is accrued out, which we can call as combination of Captcha as a graphical password (CaRP) and VRK. CaRP is a complex and innovative technique using graphical style password. CaRP solves the issues of a number of attacks, such as online guessing attacks, relay attacks, shoulder-surfing attacks etc. CaRP alone becomes inefficient to prevent all security; hence this paper makes a survey of the various security measures for secure password schemes and gives a clear picture of the efficiencies of the different techniques. There is no panacea, but highly secure password offers reasonable security and usability and appears suit well with practical applications for improving online security.